2010
DOI: 10.1108/07378831011076648
|View full text |Cite
|
Sign up to set email alerts
|

Improving the search experience: federated search and the library gateway

Abstract: Purpose -The aim of this paper is to review the evolving nature of the library web site with a focus on improving the usability of the access points to licensed and unlicensed research databases. Design/methodology/approach -The paper describes the milestones in the development of a library gateway and the incorporation of federated search into a prominent place in the gateway. Findings -Technological developments present new opportunities to extend the functionality of library systems. Achieving simplicity am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Jerry Caswell and John D. Wynstra studied the implementation of Ex Libris MetaLib centralized indexes based on the federated search technology at the University of Northern Iowa Library. [8] They confirmed how the easily accessible unified interface helped users to search multiple relevant databases simultaneously and more efficiently. Lyle Ford concluded that the Summon discovery layer by Serials Solutions fulfilled students' expectations to be able to search books and articles together.…”
Section: Related Work Discovery Layersmentioning
confidence: 50%
See 2 more Smart Citations
“…Jerry Caswell and John D. Wynstra studied the implementation of Ex Libris MetaLib centralized indexes based on the federated search technology at the University of Northern Iowa Library. [8] They confirmed how the easily accessible unified interface helped users to search multiple relevant databases simultaneously and more efficiently. Lyle Ford concluded that the Summon discovery layer by Serials Solutions fulfilled students' expectations to be able to search books and articles together.…”
Section: Related Work Discovery Layersmentioning
confidence: 50%
“…Google and Amazon), (3) Enriched content (e.g. book cover images, ratings and comments), (4) Faceted navigation for search results, (5) Simple keyword search on every page, (6) More precise relevancy (with circulation statistics a contributing factor), (7) Automatic spell check, (8) Recommendations to related materials (common in commercial sites, e.g. Amazon), (9) Allowing users to add data to records (e.g.…”
Section: Related Work Discovery Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Jefcoate 4 described that the project was launched with the aim of providing a well-founded service and building up exposure of British Library services and collections by adding home pages for directorates and departments. Caswell & wynstra 1 shared their experience about library gateway and elaborated that the gateway is all about providing new opportunities and extends the functionality of library systems. Achieving simplicity among the complex array of bibliographic and full-text resources is critical.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Knowledge Gateway at St. Stephen's College is an attempt to construct a single search service to save the time of users. Therefore, advancement of a gateway, adding meta searching and other tools into it have resulted in greater control over the way resources are presented to the user community 1 .…”
Section: Introductionmentioning
confidence: 99%